Verification and application of the extended spectral deconvolution algorithm (SDA+) methodology to estimate aerosol fine and coarse mode extinction coefficients in the marine boundary layer - K. C. Kaku; J. S. Reid; N. T. O'Neill; P. K. Quinn; D. J. Coffman; T. F. Eck (Atmospheric Measurement Techniques, 2014)
The spectral deconvolution algorithm (SDA) and SDA+ (extended SDA) methodologies can be employed to separate the fine and coarse mode extinction coefficients from measured total aerosol extinction coefficients, but their common use is currently limited to AERONET (AErosol RObotic NETwork) aerosol optical depth (AOD). Here we provide the verification of the SDA+ methodology on a non-AERONET aerosol product, by applying it to fine and coarse mode nephelometer and particle soot absorption photometer (PSAP) data sets collected in the marine boundary layer. Using data sets collected on research vessels by NOAA-PMEL(National Oceanic and Atmospheric Administration – Pacific Marine Environmental Laboratory), we demonstrate that with accurate input, SDA+ is able to predict the fine and coarse mode scattering and extinction coefficient partition in global data sets representing a range of aerosol regimes. However, in low-extinction regimes commonly found in the clean marine boundary layer, SDA+ output accuracy is sensitive to instrumental calibration errors. This work was extended to the calculation of coarse and fine mode scattering coefficients with similar success. This effort not only verifies the application of the SDA+ method to in situ data, but by inference verifies the method as a whole for a host of applications, including AERONET. Study results open the door to much more extensive use of nephelometers and PSAPs, with the ability to calculate fine and coarse mode scattering and extinction coefficients in field campaigns that do not have the resources to explicitly measure these values.